(untitled) (Bangladesh Medical Journal, 2016)
A cross-sectional, descriptive type of study was done was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from August 2005 to December 2006, based on collection of 75 postmortem male human pancreas, to determine the number of alpha and beta cells per islet of Langerhans in different parts of the pancreas with advancing age. The collected samples were divided into seven age groups, i.e. A (10-19 years), B (20-29 years), C (30-39 years), D (40-49 years), E (50-59 years), F (60-69 years) and G (?70 years), for convenient description of their various age related changes. Histological slides were prepared by using Gomoris chromium haematoxylin phloxine stain. The number of alpha and beta cells per islet of Langerhans was measured by point counting technique on a grid square drawn by Visio basic 2000 software with high magnification under the compound light microscope. The mean number of alpha cells per islet in the head of the pancreas were 17.60±2.51, 21.40±2.07, 27.40±3.13, 20.80±2.59, 15.40±2.51, 14.60±3.58 and 11.40±1.67; in the body of the pancreas were found 24.60±1.67, 31.40±2.60, 40.00±2.45, 26.80±2.05, 22.60±2.51, 19.20±2.68 and 20.00±2.45; in the tail region were 37.80±4.09, 42.20±4.82, 53.20±2.94, 55.60±6.69, 43.60±6.69, 39.20±8.01 and 35.60±1.34 in group A, B, C, D, E, F and G respectively. The mean number of beta cells per islet in the head of the pancreas were 32.60±2.51, 36.40±2.07, 42.40±3.13, 35.80±2.59, 30.40±2.51, 29.60±3.58 and 26.40±1.67; in the body of 141 the pancreas were found 39.60±1.67, 46.40±2.07, 55.00±2.45, 41.80±2.05, 37.60±2.51, 34.20±2.68 and 35.00±2.45; in the tail region were 52.80±4.09, 57.20±4.82, 68.20±2.94, 69.50±6.58, 70.60±6.69, 58.20±8.01 and 50.60±1.34 in group A, B, C, D, E, F and G respectively. In the present study, the number of alpha cells of islets of Langerhans gradually increased up to the 4th decade of life in head and body of the pancreas and up to the 5th decade in the tail region, later it decreased. Besides, the number of beta cells gradually increased up to the 4th decade of life in head and body of the pancreas and up to the 6th decade in the tail region, then decreased. Here, females were excluded due to less availability of the female cadaveric pancreas during study period. Bangladesh Med J. 2014 Sep; 43 (3): 141-145